Working Environment dan Reward terhadap Kinerja Karyawan dengan Kerjasama Tim sebagai Variabel Intervening pada PT. Bank Nagari - Yuli Angraini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to see the extent of the influence of Working environment and Rewards on Employee Performance with Teamwork as an intervening variable. The sample selection technique used random sampling and obtained 140 samples. The data analysis technique uses Structural Equition Modeling (SEM) Analysis with Partial Least Square (PLS). Based on the results of the research and hypothesis testing that has been carried out, the results of the study can be concluded that the Working environment has a positive and significant effect on Teamwork at PT. Bank Nagari Padang. Rewards have a positive and significant effect on Teamwork at PT. Bank Nagari Padang. The working environment has a positive and significant effect on Employee Performance at PT. Bank Nagari Padang. Rewards have a positive and significant effect on Employee Performance at PT. Bank Nagari Padang. Teamwork does not have a significant effect on Employee Performance at PT. Bank Nagari Padang. The working environment does not have a significant effect on Employee Performance through Teamwork as an intervention at PT. Bank Nagari Padang. Rewards do not have a significant effect on Employee Performance through Teamwork as an intervention in PT. Bank Nagari Padang.